CFAP410 has a bimodular architecture with a conserved surface patch on its N-terminal leucine-rich repeat motif for binding interaction partners - Stadler, Alexander; Gabriel, Heloisa B.; De Liz, Laryssa V.; Alonso-Gil, Santiago; Deng, Xuan; Crickley, Robbie; Korbula, Katharina; Mikolaskova, Barbora; Vaughan, Sue; Huang, Kaiyao; Žagrović, Bojan; Sunter, Jack D.; et al. (Frontiers in Cell and Developmental Biology, 2025)
Cilia and flagella associated protein 410 (CFAP410) is a protein localized at the basal body of cilia/flagella and plays essential roles in ciliogenesis. Multiple single amino acid mutations in CFAP410 have been identified in patients. However, the molecular mechanism for how the mutations cause these disorders remains poorly understood due to a lack of high-resolution structures of the protein. Our studies demonstrate that CFAP410 adopts a bimodular architecture. We have previously reported our structural studies on the C-terminal domain (CTD) of CFAP410 from various organisms. Here we report a 1.0-Å resolution crystal structure of the N-terminal domain (NTD) of Trypanosoma brucei CFAP410. We further examined how the disease-causing mutations in this domain may affect the folding and structural stability of CFAP410. Our results suggest that the single-residue mutations in the CFAP410-NTD cause human diseases by destabilizing the structure that subsequently disrupts its interaction with other partners.